Eigenspectrum-based extended Luenberger observers for a class of distributed parameter systems - Xiao, Tengfei; Li, Xiao-Dong (Journal of process control, 2020)
State estimation is an important problem in distributed parameter system especially with nonlinear dynamics in industrial process. An extended Luenberger observer based on the eigen-spectrum of the system operator is developed in this paper to handle this problem. The distributed parameter system is projected into a finite-dimensional subspace where a low-order ordinary differential equation describing the dominant dynamics of the system is derived. A Luenberger observer extended with a nonlinear part is developed based on that dominant dynamics. A sufficient condition is given in this paper for the convergence of the estimated error. Finally, by applying the developed design method to the temperature estimation of a catalytic rod, the achieved simulation results show the effectiveness of the proposed observer. •Extended Luenberger observer is developed for distributed parameter system.•An ordinary differential equation describing the dominant dynamics is derived.•A sufficient condition for the convergence of the observer error is given.•The temperature distribution of a catalytic rod is estimated.